Mannan binding lectin attenuates double‐stranded RNA‐mediated TLR3 activation and innate immunity. Issue 6 (11th February 2014) - Liu, Hongzhi; Zhou, Jia; Ma, Di; Lu, Xiao; Ming, Siqi; Shan, Guiqiu; Zhang, Xiaoyong; Hou, Jinlin; Chen, Zhengliang; Zuo, Daming
Abstract : Mannan binding lectin (MBL) functions as a pattern recognition molecule (PRM) which is able to initiate complement activation. Here, we characterize a previously unrecognized attribute of MBL as a double‐stranded RNA (dsRNA) binding protein capable of modifying Toll like receptor 3 (TLR3) activation. MBL interacts with poly(I:C) and suppresses poly(I:C)‐induced activation of TLR3 pathways and subsequent cytokine production. In addition, MBL binds to TLR3 directly. Surprisingly, disrupting the interaction between MBL and complement receptor 1 (CR1) or restraining the traffic of MBL to phagosome reversed the MBL limited TLR3 activation. We demonstrate the importance of MBL guided ligands intracellular localization, emphasizing the significance of understanding the dynamics of TLR agonists complexed with MBL or other PRMs inside the cell in immune defense. Abstract : MBL attenuates poly(I:C)‐induced TLR3 activation. MBL interacts with poly(I:C) via its CRD in a calcium dependent manner. MBL can bind to TLR3 and internalized MBL partially colocalizes with TLR3. Restraining the traffic of MBL to the phagosome can reverse the MBL limited TLR3 activation.